Beban Sosial dan Tekanan Peran Tokoh Kaluna dalam Novel Home Sweet Loan - Helennisa Febrya; Kurnia Rachmawati; Dicky Rachmat Pauji (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the social burden and role pressure experienced by the character Kaluna in Almira Bastari's work entitled Home Sweet Loan. The problems that arise are caused by an imbalance in the social roles that Kaluna must perform as a member of the sandwich generation, who has responsibilities not only for her personal needs but also for the demands of her family and social environment. The gap between social reality and cultural expectations reflects the structural pressures that influence the character's actions and decisions. The purpose of this study is to describe the social burdens and gender role pressures experienced by the character, as well as to interpret their social meaning from a literary sociology perspective. The method used in this study is descriptive qualitative with observation and recording techniques to collect data in the form of relevant quotations from the novel text. The findings of this study show that Kaluna faces pressures related to economics, family demands, and gender expectations that require her to perform roles in both the domestic and public spheres simultaneously. Gender role pressure arises through the demand to appear as an ideal woman, while social burdens arise from financial responsibilities and expectations of an unbalanced role. In conclusion, the novel Home Sweet Loan depicts the complexity of the lives of young women from the urban middle class who are trapped in demanding social structures, providing a realistic picture of social burdens and role pressures in modern society.